Defining clinical subgroups and genotype-phenotype correlations in NBAS-associated disease across 110 patients - Staufner, Christian; Leibner, Alexander; Moog, Ute; Diwan, Gaurav; Dikow, Nicola; Russell, Robert B.; Garbade, Sven; Kölker, Stefan; Hoffmann, Georg F.; Lenz, Dominic (Genetics in medicine, 2020)
Pathogenic variants in neuroblastoma-amplified sequence (NBAS) cause an autosomal recessive disorder with a wide range of symptoms affecting liver, skeletal system, and brain, among others. There is a continuously growing number of patients but a lack of systematic and quantitative analysis. Individuals with biallelic variants in NBAS were recruited within an international, multicenter study, including novel and previously published patients. Clinical variables were analyzed with log-linear models and visualized by mosaic plots; facial profiles were investigated via DeepGestalt. The structure of the NBAS protein was predicted using computational methods. One hundred ten individuals from 97 families with biallelic pathogenic NBAS variants were identified, including 26 novel patients with 19 previously unreported variants, giving a total number of 86 variants. Protein modeling redefined the β-propeller domain of NBAS. Based on the localization of missense variants and in-frame deletions, three clinical subgroups arise that differ significantly regarding main clinical features and are directly related to the affected region of the NBAS protein: β-propeller (combined phenotype), Sec39 (infantile liver failure syndrome type 2/ILFS2), and C-terminal (short stature, optic atrophy, and Pelger-Huët anomaly/SOPH). We define clinical subgroups of NBAS-associated disease that can guide patient management and point to domain-specific functions of NBAS.
Published online: 25 November 2019
Gesehen am 15.04.2020